Heart Rate Changes Before, During, and After Treadmill Walking Exercise in Normal Dogs - Shull, Sarah A.; Rich, Sarah K.; Gillette, Robert L.; Manfredi, Jane M. (Frontiers in Veterinary Science, 2021)
Changes in heart rate (HR) can reflect fear, pain, anticipation, and conditioning in dogs, yet it is not routinely assessed in veterinary rehabilitation patients. Knowing expected HR changes during rehabilitation exercises can guide protocols and optimize post-operative therapy. The study’s primary objectives were to: assess HR in dogs undergoing treadmill exercise (TE) and compare three HR collection techniques (auscultation, the KER ClockIt monitor (ClockIt), and the Dextronix VetScoutPlus Holter (VetScout)). We hypothesized that HR would increase during TE, that HR taken immediately after TE would not reflect HR during TE, and that all measurement methods would be similar. HR was recorded in all methods simultaneously in eight adult healthy large breed dogs during rest (REST), immediately before TE (PRE), during TE (WALK), and after TE (POST). Statistical analyses included Spearman Correlations, Bland-Altman analyses, and repeated-measures ANOVAs with Sidak’s post-hoc test (significant at P<0.05).TE exercise significantly increased HR during WALK in both VetScout and ClockIt. Auscultation was not possible during WALK. Elevations in HR during WALK were not reflected in POST. Significant strong correlations (rho=0.9, P <0.01) existed between VetScout and ClockIt at REST and WALK and between VetScout and auscultation at REST, PRE, and POST. Auscultation and ClockIt only significantly correlated at REST (rho= 0.9, P=0.002). The main limitation was only healthy and large breed dogs were used. Both monitors could capture the increase in HR during exercise and could guide TE regimens in real-time to minimize patient risk.